Cytotoxic, antiglycation and carbonic anhydrase inhibition studies of chromium(III)-aroylhydrazine complexes - Shamshad, Bushra; Jamal, Rifat Ara; Ashiq, Uzma; Mahroof-Tahir, Mohammad; Saleem, Muhammad (European Journal of Chemistry, 2018)
In order to further reveal the chemistry and biochemistry of chromium(III) complexes, the present work illuminates the formation of chromium(III) complexes with aroylhydrazine ligands with their physical, chemical and spectral studies. Another significant contribution of this study is the evaluation of the cytotoxic activity, antiglycation property and carbonic anhydrase inhibition study of synthesized chromium(III)-aroylhydrazine complexes. Synthesis and structural investigation of aroylhydrazine ligands (1-7) and their chromium(III) complexes (1a-7a) were carried out by using elemental analysis (C, H, N), physical (conductivity measurements) and spectral (EI-Mass, ESI-Mass, FTIR and UV-Visible) methods. These physical, analytical and spectral data supports that all chromium(III)-aroylhydrazine complexes exhibit an octahedral geometry in which ligand exhibits as a bidentate coordination and two water molecules coordinated at equatorial positions with general formula [Cr(L)2(H2O)2]Cl3. Cytotoxic investigations shows that synthesized chromium(III)-aroylhydrazine complexes were not found to be toxic against normal cells so these compounds were further studied for other biological activities. Moreover, aroylhydrazine ligands and their chromium(III) complexes were examined for their antiglycation activity in which ligands were found inactive whereas chromium(III)-aroylhydrazine complexes showed significant inhibition of the process of protein glycation. Similarly, in carbonic anhydrase inhibition studies all aroylhydrazine ligands were observed inactive while some of chromium(III)-aroylhydrazine complexes showed potential in carbonic anhydrase inhibition.